The influence of marketing mix towards purchase decision of pocari sweat product - Ch. Endah Winarti; Rheza Dwi Andzar; Yohanes Ferry Cahaya; Annathasia Puji Erasashanti (Institute of Computer Science (IOCS), 2023)
Huge competition in the bottled water industry drives the companies to choose the right strategy to apply. The purpose of this research is to evaluate the role of quality of product, price as well as promotion in increasing purchase decision for Pocari Sweat products. Quantitative descriptive has been chosen as research method. Research population was gathered from those consumers who have drink up Pocari Sweat through nonprobability sampling as Sampling method used which obtained 75 respondents. The data was earned from questionnaires results which then proceeded by multiple linear regression analysis as Technical analysis with the assist from SPSS statistics version 26.0 for windows program. And it is found that (1) product quality has no meaning in affecting purchase decision (2) price has significantly positive in affecting purchase decision (3) promotion has significantly positive in Influencing purchasing decision.